Automated methods for quantifying the tortuosity of microvascular networks - Dodd, Melody, author; Putkaradze, Vakhtang, advisor; Tobet, Stuart, committee member; Shipman, Patrick, committee member (Colorado State University. Libraries, 2012)
Networks of microscopic blood vessels can be studied for changes in morphology that correlate with biological abnormalities. Tortuosity, or vessel twistiness, is one of these morphological properties, and it can be surprisingly difficult to quantify. The purpose of this thesis is to present the development, testing, and analysis of new automated methods to measure and quantify the tortuosity of microvascular networks. We will explain necessary automated image processing techniques and background information before presenting our new metrics for measuring network tortuosity. Experiments using the methods will be presented, including a full analysis of the results. We will use the results from these experiments to justify our final conclusions and recommendations regarding the performance of the methods.